Exploring the Potentials of Project-based Transnational Entrepreneurship Education - A Single Case Study in Namibia. - Aki Harima; Cat My Dang (My University, 2019)
Exploring the Potentials of Project-based Transnational Entrepreneurship Education - A Single Case Study in Namibia.
Keywords: Entrepreneurship education